2021
DOI: 10.1007/s00262-021-02947-y
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 coupled with IL-12 increases intratumoral T cell clonality, leading to complete regression of non-immunogenic tumors

Abstract: Immune checkpoint inhibitors against PD-1, PD-L1 and CTLA-4 have altered the treatment paradigm for various types of cancers in the past decade. However, they offer clinical benefits to only a subset of patients. Evaluation and identification of an appropriate therapeutic approach to improve intratumoral immune status are needed for better treatment outcomes. We previously demonstrated that intratumoral expression of IL-7 and IL-12 increased tumor-infiltrating lymphocytes in poorly immunogenic tumors, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Mamoru et al. demonstrated that when IL-7 was induced in the presence of IL-12, the diversity of intratumoral CD8+ T cells increased, and IL-12 function was augmented to promote clonality ( 22 ). Similarly, immunocomplexes of IL-7 and αIL-7 mAb M25 (IL-7/M25) were described as super-agonists, remarkably augmenting the size of the T-cell pool.…”
Section: Il-7/il-7r and T Cellsmentioning
confidence: 99%
“…Mamoru et al. demonstrated that when IL-7 was induced in the presence of IL-12, the diversity of intratumoral CD8+ T cells increased, and IL-12 function was augmented to promote clonality ( 22 ). Similarly, immunocomplexes of IL-7 and αIL-7 mAb M25 (IL-7/M25) were described as super-agonists, remarkably augmenting the size of the T-cell pool.…”
Section: Il-7/il-7r and T Cellsmentioning
confidence: 99%
“…Mamoru et al reported that IL-7 and IL-12 expression of recombinant vaccinia viruses increased tumor-infiltrating lymphocytes in the LLC lung cancer model, leading to a better tumor therapy efficacy than IL-12 alone. And they demonstrated that IL-7 and IL-12 combination virotherapy could increase the intratumoral CD8 + T cells clonality and anti-tumor response rate as well [ 29 ]. The synergistic effect of IL-12 and IL-18 has also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the absence of altered thymic output – which is deemed largely insufficient for maintenance of naïve T cell frequency in older age ( 143 145 ) – it may be the case that naïve T cells are instead maintained extra-thymically via homeostatic turnover ( 143 ) chiefly via cytokines including IL-7 ( 104 ). There is evidence from human studies that recombinant IL-7 administration can increase the T cell repertoire ( 146 ), and this process may culminate in enhanced eradication of previously non-immunogenic tumours ( 147 ). Therefore, given that physical activity – and specifically skeletal muscle – is implicated in elevated levels of homeostatic cytokines such as IL-7, it may be the case that physical activity does indeed maintain naïve T cells ( 109 , 127 ), however more research is needed to confirm these observations.…”
Section: Part 3: Evaluating the Effects Of Physical Activity On T-cel...mentioning
confidence: 99%